Cross-Cultural Considerations in U.S. Research Ethics Education - Heitman, Elizabeth (J Microbiol Biol Educ, 2014)
Demand among graduate and postdoctoral trainees for international research experience brings together students and investigators from increasingly diverse cultural backgrounds around the world. Educators in research ethics and scientific integrity need to address the cultural aspects of both science and ethics to help all trainees learn ethical practices for effective collaboration with a diverse array of partners. NIH and NSF’s mandates for instruction in the responsible conduct of research do not specifically address the needs of international trainees or U.S. trainees who undertake research projects abroad. Nonetheless, research ethics educators’ typical focus on policy and professional standards can offer trainees and faculty investigators helpful insights into differing ethical values and priorities in research. Examination of linguistic differences can also reveal important conceptual frameworks that shape ethical practice. New resources for teaching research integrity in cross-cultural settings can be a valuable addition to the development of shared understanding of the goals of scientific research.